Light field 3D reconstruction for holographic-like display - Ong, Kien Seng (2016)
In this project report, we focuses on Tensor Display, a form of compressive light field display. Firstly, research study had been done to better understand the technology involved in the light field reconstruction. This is important as the basic concept would be required to recreate a new prototype which would be an enhancement of the current one we have in NTU in terms of both the hardware and software. This new Tensor display prototype would then be used to carry out further experiments to improve on the 3D quality display on this technology. Some of the experiments include the crucial colour and luminance that have a great impact on 3D display imaging, the field of view and depth of view which allows user to have a better 3D experience. Finally, there are some recommendations for future works to tackle the issues we observed in the experiment that affect the 3D display.